Time and old age: the object as memory device (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This work aims to foster relationships between the old, time and objects as a memory device. The first stage of creation of the new work by the Brasilia collective Entrevazios will be approached from a different perspective on the object and the personal stories of elderly women who left their hometowns to try life in the territory of the new federal capital. In the months of August to October 2023, stories of elderly women were heard and recorded in four administrative regions of the Federal District based on the “Barraca de Memórias” action. The reports will become a mini documentary and later the dramaturgy of a scenic-installation work in Object Theater.
Keywords: time; elderly; aging; memory; objects; Brasília